The Social Capital and Firm Performance: Evident from Indonesia Small businesses - Pratono, Aluisius Hery; Saputra, Ruswiati Surya; Pudjibudojo, Jatie K. (International Journal of Economics and Financial Issues, 2016)
This study aims to contribute to the social capital theory through examining the direct impact of social capital and moderating impact of marketing capability on firm performance. This study proposes a structural equation model and tests the hypothesis through generalized structured component analysis (Gesca) with random survey on small medium enterprises in Indonesia. The approach allows to analysis the ellement of social capital: network, trust and cognitive as well as the ellements of marketing capability: pricing capability, product development, and marketing communication. The result indicates the social capital and marketing capability provide complementary effect to the firm performance. Keywords: social capital; firm performance; marketing capability JEL Classifications: D21, L30, M31